Experimental study on the efficiency improvement of a forced draft wet cooling tower via magnetic Fe3O4 nanofluid and optimized packing - Mohammad Nakhaee Sharif; Hamidreza Goshayeshi; Reza Saleh; Issa Chaer; Davood Toghraie; Soheil Salahshoor (Case Studies in Thermal Engineering)
The thermal performance of wet cooling towers is often limited by the low heat transfer capacity of conventional working fluids and suboptimal packing designs. To address this challenge, this study presents an experimental investigation of a laboratory-scale forced-draft counterflow wet cooling tower. The effects of Fe3O4/water magnetic nanofluid, magnetic field orientation, and three types of packing geometries (splash and film fills) were evaluated under various flow conditions. Key performance parameters—including the Merkel number, thermal efficiency, outlet water temperature, and cooling range—were analyzed. Employing 0.15 wt% Fe3O4/water nanofluid under a magnetic field led to a 55 % increase in the Merkel number, a 37 % rise in thermal efficiency, a 14 % reduction in outlet temperature, and a 27 % improvement in cooling range compared to pure water. Among the tested packings, the splash type demonstrated the best performance due to enhanced droplet breakup and increased surface area, resulting in an average increase of 187 % in the Merkel number compared to towers without packing. This is the first experimental study to jointly assess the influence of magnetic nanofluid, magnetic field configuration, and packing type on wet cooling tower performance. These findings provide new insights for enhancing energy efficiency in cooling systems by utilizing advanced working fluids and optimized internal components.